Elazığ için Çok Fonksiyonlu Bir Proje Çalışması: Botanik Park, Pompa Sulama Hattı ve Güneş-Hidroelektrik Santrali - Aytaç, Ayça (Fırat University, 2024)
Kentsel merkezler, sadece ekonomik faaliyetlerin merkezleri olmakla kalmaz; aynı zamanda topluluk yaşamı ve sosyal etkileşimin odak noktalarıdır. Bu kentsel ortamlardaki yaşam standartlarını yükseltmek, yerel yönetimlerin sorumluluğundadır. Bu amaçla, birçok gelişmiş şehirde botanik bahçeleri ve rekreasyon alanları kurulmuştur. Bu tesisler, sadece yerel halkın ve faunanın yaşamını zenginleştirmekle kalmaz, aynı zamanda yerel ekonomiye de önemli katkılarda bulunurlar. Kent ekonomilerindeki bu önemli rolü tanıyarak, Elazığ'ın merkezinde böyle bir tesis kurma gerekliliği ortaya çıkmaktadır. Bu çalışma, belirlenen alan içinde bir botanik bahçesi kurulmasının fizibilitesinin ön değerlendirmesini yapmakta olup, Keban Barajı rezervuarından su kullanımı, aşağı akış sularını değerlendiren mikro-hidroelektrik santral inşası gibi çeşitli projeleri incelemektedir.

Urban centers serve as more than just hubs of economic activity; they are also focal points of community life and social interaction. It is incumbent upon local authorities to elevate the standard of living within these urban environments by establishing communal spaces conducive to enhancing the well-being of residents. To this end, botanical gardens and recreational areas have been established in numerous developed cities worldwide. These amenities not only enrich the lives of inhabitants and local fauna but also constitute significant contributors to the municipal economy. Recognizing their pivotal role in urban economies, the imperative lies in implementing projects that optimize the utilization of available water resources. The prospect of establishing such a facility in the heart of Elazig holds promise. This study undertakes a preliminary assessment of the feasibility of establishing a botanical garden within the designated area, exploring avenues such as tapping into the Keban Dam reservoir, constructing a micro-hydroelectric power plant utilizing downstream water, and other potential initiatives
A Multifunctional Project Study for Elazig: Botanic Park, Pumped Irrigation Line, and Solar-Hydroelectric Power Plant
Keywords: Water Resources Engineering; Su Kaynakları Mühendisliği